Assessment of right ventricle in pulmonary arterial hypertension with three-dimensional echocardiography and cardiovascular magnetic resonance. Issue 12 (December 2021) - Lattanzio, Mariangela; Scelsi, Laura; Golino, Michele; Lattuada, Maddalena; Raineri, Claudia; Turco, Annalisa; Giuntini, Chiara; Ceriani, Francesca; Curti, Marco; Bonelli, Andrea; Piacentino, Filippo; Venturini, Massimo; et al.
Abstract : Aim: To correlate 3-D Echo and CMR RV parameters and to verify whether they are similarly related to the clinical conditions of patients with pulmonary arterial hypertension (PAH), a disease in which the RV plays a crucial prognostic role. Methods: We enrolled 34 consecutive PAH patients followed by our PAH clinics. All patients underwent a 3-D Echo and CMR assessment of RV volumes and functions in the same day. The presence or absence of correlation between major findings was investigated; functional RV parameters were also analyzed in relation to 6-min walking test (6MWT) results and BNP/Nt-proBNP plasma levels. Twenty-four subjects served as controls. Results: Good agreement was found between 3-D Echo and CMR measures of RV volumes [RV-end-diastolic volume ( r = 0.72, P < 0.0001), RV-end-systolic volume (ESV) ( r = 0.80, P < 0.0001)] and function [RV-EF ( r = 0.73, P < 0.0001), RV-ESV/SV ( r = 0.83, P = 0.001)] for all the subjects of the study. These correlations were stronger in PAH patients than in control subjects. Importantly, 3-D Echo and CMR RV-EF and RV to pulmonary arterial coupling (RV-ESV/SV) similarly correlated with BNP/Nt-proBNP levels and with functional capacity measured at 6MWT in the PAH patients group. Conclusions: 3-D Echo demonstrated a significant agreement with CMR in the assessment of RV volume and function in PAH patients. Both techniques showed a similar correlation with clinical and prognostic parameters. The use of 3-D Echo should be amply boosted in the real-world clinical evaluation of PAH patients. Abstract : Supplemental Digital Content is available in the text